Validity and reliability of an protocol of the stomatognathic and postural system evaluation for patients with obstructive sleep apnea: a cross-sectional study - Guijarro-Herraiz, Marta; Arias Palencia, Natalia M.; Mayordomo, Maria Figueroa; Palomo Carrión, Rocío; Notario Pacheco, Blanca (Frontiers in Physiology, 2025)
IntroductionMyofunctional therapy has been used for years as an intervention with high effectiveness in cases of Obstructive Sleep Apnea (OSA). Until now, little importance has been given to postural attitude or morphotype), even though these can modify the state in which we find the musculature and fascial system of the entire stomatognathic system. The objective if this cross-sectional study is to analyse the validity and reliability of a stomatognathic and postural systems assessment protocol for patients with OSA.MethodsThis is a cross-sectional study that uses new observational and measurement parameters (the postural attitude or morphotype, the position of the hyoid bone, potential temporomandibular joint disorders and mobility of the spheno-basilar joint), were assessed in 105 adult subjects presenting with symptoms associated with obstructive sleep apnea (OSA). All subjects were evaluated using the same guidelines and standardized tests. Participants ranged in age from 23 to 83 years and volunteered to take part in the study. The assessment followed a specific protocol encompassing two main components (A) postural analysis and (B) specific evaluation of the stomatognathic system. All measurements were conducted by the same examiner (MMGH), thereby minimizing interobserver bias.ResultsCriterion validity was assessed using two Spearman correlation tests. The first examined the correlation between the final protocol score and the apnea-hypopnea index (AHI), yielding a value of 0.082. The second analysis assessed the correlation between the diagnostic results from sections A and B of the protocol, with correlation coefficients of 0.824 and 0.907 respectively. Concurrent validity was evaluated using Spearman correlation between the final protocol score and several variables: apnoea–hypopnoea index, Epworth Sleepiness Scale, physical activity, waist circumference, and neck circumference. All correlations were statistically significant (p < 0.01; p < 0.05). An ANCOVA was conducted to examine mean differences in variables across categories of the final protocol score, controlling for age and sex. Internal consistency of the scale was assessed using Cronbach’s alpha, which yielded a coefficient of 0.926. Reproducibility of the protocol was evaluated using the standardised intraclass correlation coefficient (ICC).ConclusionThe specific protocol for the evaluation of the stomatognathic and postural system for OSA (SPOSAP) is a valid and reliable instrument for the screening of the pathology. We believe that the validation of this protocol may facilitate the identification of undiagnosed patients presenting with compatible symptomatology, and broaden the range of treatment options currently available.